From Plato to Beauvoir: A Study on the Body - Cep Gilang Fikri Ash-Shufi (Penerbit Hellow Pustaka, 2025)
The Western concept of the body has existed since Greek times, with diverse perspectives. In ancient times, thinking about the body revolved around the dualism between body and soul. For Socrates, for example, the body was a prison for the soul. Furthermore, Plato is considered a Greek figure who extensively discussed the dualism between body and soul. He argued that the body can perish, while the soul remains immortal. The two are unrelated; if the body is glorified, the soul becomes debased, and vice versa. Unlike Plato, who considered a dualism between body and soul, Aristotle argued that body and soul are inseparable. He believed that the soul is united with the body, just as the function of sight or the ability to cut is united with what supports it: the eye or the axe. This concept of the body, namely the dualistic-monistic view, has been around since Greek times.